2021
DOI: 10.1111/jcmm.17037
|View full text |Cite
|
Sign up to set email alerts
|

MET inhibition enhances PARP inhibitor efficacy in castration‐resistant prostate cancer by suppressing the ATM/ATR and PI3K/AKT pathways

Abstract: Up to 30% of patients with metastatic castration‐resistant prostate cancer (CRPC) patients carry altered DNA damage response genes, enabling the use of poly adenosine diphosphate–ribose polymerase (PARP) inhibitors in advanced CRPC. The proto‐oncogene mesenchymal–epithelial transition (MET) is crucial in the migration, proliferation, and invasion of tumour cells. Aberrant expression of MET and its ligand hepatocyte growth factor is associated with drug resistance in cancer therapy. Here, we found that MET was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
(98 reference statements)
1
11
0
Order By: Relevance
“…This agrees also with the recent report that increased MET protein expression was found in primary cultures of PARPi resistant high-grade serous ovarian carcinomas [ 41 ]. Again, in line with data reported here, it has been recently shown that in cellular models of castration-resistant prostate cancer, MET inhibition enhances the efficacy of PARPi by suppressing the ATM /ATR and PI3K/AKT pathways [ 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…This agrees also with the recent report that increased MET protein expression was found in primary cultures of PARPi resistant high-grade serous ovarian carcinomas [ 41 ]. Again, in line with data reported here, it has been recently shown that in cellular models of castration-resistant prostate cancer, MET inhibition enhances the efficacy of PARPi by suppressing the ATM /ATR and PI3K/AKT pathways [ 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…MCPH1 recruits ATM and NBN to DNA damage repair foci as part of the early DNA damage response [ 50 ]. The functional loss of ATM or NBN, two genes that are downregulated in our study, is associated with poor survival in PCa patients [ 50 , 51 , 52 ] and sensitizes PARP inhibitor therapies. Androgen receptor splice variant expression, in contrast, appears to reactivate DNA damage repair gene expression previously thwarted by ADT.…”
Section: Discussionmentioning
confidence: 92%
“…The biological importance of this is underscored by our finding that three differentially drug-responsive motility phenotypes co-occur in parallel in drug-resistant PC3M-D R cells, including a non-elongated shape, yet highly motile phenotype. Notably, Met levels and signalling are upregulated in advanced prostate cancer patients, associated with Olaparib-resistance in prostate cells and regulate invasion in vitro and tumourigenesis in vivo 55 , suggesting that such phenotype plasticity might be a general feature of drug-resistant cells.…”
Section: Discussionmentioning
confidence: 99%